Nest attentiveness does not impact incubation duration across different bird species - D. Charles Deeming (Avian Research)
Avian incubation is characterised by the contact between the eggs and the bird's skin to transfer heat to increase egg temperature above ambient conditions. Birds can be attentive to the clutch all of the time or, particularly if only one parent incubates, attentiveness may be quite low. Attentiveness is related to egg size with large eggs having high attentiveness, whereas small eggs (<10 g) can have attentiveness ranging from 50% to 100%. Previous studies have suggested that incubation duration is a function of attentiveness albeit for small birds. This study tested the hypothesis that, after controlling for egg size and phylogeny, incubation duration would be a function of attentiveness. Data for 444 bird species representing 24 orders were analysed. Whilst egg mass had a significant relationship with incubation duration, there was no relationship with attentiveness for all of the species or a subset of the passerines. Despite egg temperature drops during an incubation recess, average day-time and night-time temperatures are similar in a range of species. Re-examination of previously reported temperature profiles recorded by dummy eggs over a 24-h period shows that after an incubation recess there seems to be an additional heat flux that raises egg temperature above that seen during night-time periods of constant incubation. The reasons why eggs under intermittent incubation are not considerably cooler than eggs during constant incubation are discussed.